2016
DOI: 10.1038/onc.2015.487
|View full text |Cite
|
Sign up to set email alerts
|

HER2 drives Mucin-like 1 to control proliferation in breast cancer cells

Abstract: Mucin-like 1 (MUCL1) was first identified as a breast-specific gene over a decade ago. Based on its highly restricted mRNA expression in breast tissue and continued expression during breast tumorigenesis and progression, MUCL1 is an attractive tumor-associated antigen and a potential therapeutic target. However, very little is known about the cellular location, biological functions and regulation of the MUCL1 protein, which will have a major impact on its druggability. Here we describe our efforts to fully cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 23 publications
(25 reference statements)
1
31
0
2
Order By: Relevance
“…In accordance with our results, it was previously shown that human monocyte-derived DC increased expression of Cyp24a1 in response to vitamin D3 [24]. Mucl1 has previously been identified as breast cancer-specific gene whose product Mucin-like protein 1 controls proliferation in breast cancer cells [25]. The protein is present intracellularly or secreted from the cancer cells.…”
Section: Comparison Of the Selected Gene Expression In DC Obtained Frsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our results, it was previously shown that human monocyte-derived DC increased expression of Cyp24a1 in response to vitamin D3 [24]. Mucl1 has previously been identified as breast cancer-specific gene whose product Mucin-like protein 1 controls proliferation in breast cancer cells [25]. The protein is present intracellularly or secreted from the cancer cells.…”
Section: Comparison Of the Selected Gene Expression In DC Obtained Frsupporting
confidence: 92%
“…The protein is present intracellularly or secreted from the cancer cells. FAK/JNK pathway was identified as the downstream effector of MUCL1 signaling [25]. High expression of MUCL1 in human and rat tolDC implies that this protein might play an important role in tolerogenic activity of DC.…”
Section: Comparison Of the Selected Gene Expression In DC Obtained Frmentioning
confidence: 99%
“…BC has been recognized to be immunogenic, which has involved multiple putative tumor-associated antigens (TAAs), such as HER-2 and Mucin 1 (MUC1) [30,31]. Note worthily, these TAAs have been treated as the targets for developing new cancer vaccine and bispeci c antibody (bsAbs) over the past decade, among which, some have been translated into tumor-speci c immune responses and have been veri ed to be clinically bene cial [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various autoantibodies against membranous and serum proteins, which are easily bound by autoAbs, are frequent in sarcoidosis patient sera. These antibodies (autoAbs against tumor necrosis factor receptor superfamily member 14 (TNFRSF14) [57], growth differentiation factor 10 {GDF10 (BMP3)} [58], mucin-like protein 1 (MUCL1) [59], ring finger and SPRY domain containing 1 (RSPRY1) [60], RRAD and GEM like GTPase 1 (REM1) [61], and gametocyte-specific factor 1-like (GTSF1L) may be modulators of the disease course. These results suggest that autoAbs reflect the ongoing pathophysiology of the disease itself.…”
Section: Sarcoidosismentioning
confidence: 99%